Avaliação da atividade antinociceptiva do extrato bruto, das frações e dos compostos obtidos de Geissospermum vellosii - Tavares, Juliana de Abreu Werner (2008)
The present study examined the antinociceptive effects of Geissospermum vellosii in chemical behavioral models of nociception. G. vellosii crude extract, dichloromethane fraction (1-100 mg/kg), or aspidospermine (0.001-1 mg/kg), were administered by p.o. route, 60 min earlier tests. Crude extract produced inhibition of formalin-induced inflammatory nociception and acetic acid-induced visceral nociception. Dichloromethane fraction was able to produce significant antinociception in both phases of formalin and acetic acid-induced nociception. The antinociception caused by dichloromethane fraction in the acetic acid test was significantly attenuated by i.p. pre-treatment of mice with p-chlorophenylalanine methyl ester (PCPA, an inhibitor of serotonin synthesis, 100 mg/kg once a day for 4 consecutive days), or WAY-100635 (5-HT1A receptor antagonist, 0.3 mg/kg). In contrast, G. vellosii antinociception was not affected by i.p. pre-treatment of animals with ketanserin (5-HT2A receptor antagonist, 0.3 mg/kg) or ondansetron (5-HT3 receptor antagonist, 0.5 mg/kg). The isolated compound aspidospermine also was able to reduce the nociception in acetic acid test. Together, these results indicate that G. vellosii produces antinociception in models of chemical nociception through mechanisms that involve an interaction with 5-HT1A receptor of serotonergic system.